Pusat Pelatihan Pertanian Perdesaan Swadaya (P4S)di Kecamatan Mojogedang - Eko Prasetyo, Doni; , Ir. Indrawati, MT; , Rini Hidayati, ST, MT (2016)
Indonesia agriculture is still poorly reviewed from farmers welfare, still poor many hearts classes. the government program caused no maximum, focused only at farming, support the weak macro policies, as well as centralized approach. as a result of farming in indonesia is still dominated by efforts with many small scale, capital limited, simple technology, is very influenced by season, local market, agricultural commodity markets dominated by big merchant-traders. Pusat pelatihan pertanian perdesaan swadaya (P4S) di Kecamatan Mojogedang is the institute for agricultural and rural yang founded, owned, managed by farmers operates non both individual and group contributing active hearts agricultural development through the development of human resources farming hearts forms of training / apprenticeships for farmers, regarding the management of agricultural science education, agriculture quality development through research, improvement of agricultural product value by post-harvest processing. in the work of singer tried improve food security in Kecamatan Mojogedang at particular and in Indonesia in general, through an increase in quality employment in the field of agriculture, as well as creates a design architecture the permanent balancing environment. Pusat pelatihan pertanian perdesaan swadaya (P4S) di Kecamatan Mojogedang is a building (building) the building consists berberapa (compound) the structure has any group represents operating activities group. The design using eco-architecture design concept the attention to energy issues and knowledgeable environment. apply renewable technology, including cropping vertical (vertikultur) and saving irrigation system air, and utilizing natural energy, solar heat energy (solar systems) and energy potential air (air turbine). Eco-architecture approach embodied hearts conservation form conditioned, among other things, optimizing biopori infiltration, infiltration wells, rain water tanks, ensuring that local vegetation, rain reservoirs of underground air, manufacture reservoir / small lake as an attempt to improve the country stores. irrigation systems save air and water treatment systems as gray use efforts to save the air. saving electricity energy, daylighting, optimization penghawaan Natural (cross ventilation, the stack effect), optimization of solar cells and optimization of turbine with utilization of potential energy, use solar lights and led lights, optimization potential nature with system design passive mode and mixed mode design.